Role of Tc-99m pertechnetate thyroid scintigraphy in evaluation of lingual and midline neck swellings - Bhatt, Bhairavi Mohit; Pawar, Shwetal Uday; Anand, Anuja; Ghorpade, Mangala Kedar; Shetye, Suruchi Suresh (International Journal of Research in Medical Sciences, 2018)
Background: The ectopic thyroid tissue in thyroglossal cyst or suprahyoid swelling is one of most important differential to be diagnosed. The purpose of this study was to find out role of Technetium-99m Pertechnetate Thyroid Scintigraphy (TS) to detect functioning thyroid tissue in ectopic locations presenting as midline neck swelling. Methods: A retrospective observational study was done where 26 subjects presenting with midline neck swelling were included. These subjects were injected with 1-5MBq/kg of Technetium-99m Pertechnetate to perform the TS. The uptake of tracer in the midline neck swelling and in other ectopic location was assessed. The comparison with Ultrasound (USG) was also done. Results: 12 (46.15%) subjects presented with infra hyoid swelling and rest 14 (53.85%) presented with supra hyoid and submental swelling. 33.3% subjects presenting with thyroglossal duct cyst showed functioning thyroid tissue. Also 4 subjects showed dual functioning ectopic tissue. USG an TS showed concordant results for detecting thyroid tissue in ectopic location (p=0.68). However, TS performed better to detect ectopically located thyroid tissue (p=0.0086). Conclusions: USG and TS showed similar results to detect thyroid tissue in normal location. However, TS is better to detect topically located thyroid tissue. TS adds information of functioning thyroid tissue during workup of midline neck swelling.